2021
DOI: 10.1021/acsomega.0c06164
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control of the Manganese Photoluminescence in Fe3O4/l-Cys ZnS:Mn Nanocomposites

Abstract: We investigated the magnetic control of the Mn photoluminescence (PL) in iron oxide/l-cysteine-capped zinc sulfide (Fe3O4/l-cys ZnS:Mn) nanocomposites via temperature- and field-dependent PL intensity studies. Fe3O4/l-cys ZnS:Mn was synthesized following a wet chemical deposition route and then its physicochemical, morphological, and magnetic properties were characterized. X-ray diffraction analysis indicates the formation of a semiconducting composite material with coexisting phases with high crystalline qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…It is also known that the magnetic field leads to the splitting of dorbitals of Mn 2+ , thereby making the spin-selective transfer of energy more difficult. [51,52] To deeper rationalize the splitting of the ground state of Mn 2+ ions of SS-/RR-1 under the action of a magnetic field, we have performed an EPR study and magnetic circular dichroism (MCD) calculations exemplified by SS-1 (for details, see Section S15, Supporting Information). It has been found that the ground state of Mn 2+ ions of SS-1 is orbital singlet 6 S 5/2 with relatively high zero-field splitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that the magnetic field leads to the splitting of dorbitals of Mn 2+ , thereby making the spin-selective transfer of energy more difficult. [51,52] To deeper rationalize the splitting of the ground state of Mn 2+ ions of SS-/RR-1 under the action of a magnetic field, we have performed an EPR study and magnetic circular dichroism (MCD) calculations exemplified by SS-1 (for details, see Section S15, Supporting Information). It has been found that the ground state of Mn 2+ ions of SS-1 is orbital singlet 6 S 5/2 with relatively high zero-field splitting parameters.…”
Section: Resultsmentioning
confidence: 99%
“…88-0315) and those reported elsewhere. 2,7,8,[26][27][28][29] Besides, the result also demonstrated that the formation of such crystal phase and their degree of crystallinity was not affected by surface modication with aspartic acid. As shown, both unmodied and aspartic-modied Fe 3 O 4 exhibited a very similar XRD pattern.…”
Section: Resultsmentioning
confidence: 99%
“…ICP-mass spectrometry (ICP–MS) was used to determine the concentration of iron internalization in cells after being loaded with cubic ND-PEG-SPIONs. ICP–MS analysis was done using a NexION 300D ICP mass spectrometer (PerkinElmer, USA) equipped with SC4-DX autosamplers (ESI, USA) . Cells were seeded at 10 5 cells per well in 6-well plates and treated with cubic ND-PEG-SPIONs (0.000, 0.025, 0.100, 0.500 mg/mL Fe) for 24 h. Then, wells were washed abundantly with DPBS to remove free particles and centrifuged to obtain cells in pellet form.…”
Section: Methodsmentioning
confidence: 99%
“…Decomposition of the samples’ matrix was performed by heating at 70 °C for 16 h after the addition of trace metal grade nitric acid (20% aqueous solution). Digested samples were diluted (1:10) with pico-pure water and with 2% nitric acid to fit into the calibration curve . ICP–MS was operated in standard mode; all operating parameters were optimized to meet the requirements as defined by the manufacturer prior to method calibration and analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation